Surgical treatment and prognosis of 96 cases of intraductal papillary mucinous neoplasms of the pancreas: A retrospective cohort study. (January 2015) - Tian, Xiaodong; Gao, Hongqiao; Ma, Yongsu; Zhuang, Yan; Yang, Yinmo
Abstract: Introduction : The indications, the extent and type of surgery for intraductal papillary mucinous neoplasm (IPMN) are still controversial. This study aimed to investigate clinical manifestation, individualized surgical treatment, and prognosis of IPMN of pancreas.Methods : The clinical data of 96 IPMN cases treated in our hospital between January 2006 and December 2013 were retrospectively analyzed. Among the 96 patients (58 male and 38 female), 46 were main-duct type, 29 were branch-duct type, 21 were mixed type. Pancreatectomy was performed on 78 cases, including pancreaticoduodenectomy on 43 patients, distal pancreatectomy on 25, segmental pancreatectomy on 6, and total pancreatectomy on 4. A regular follow-up without surgical treatment was performed on 18 cases with asymptomatic side branch IPMN less than 3 cm in diameter. Results: The overall postoperative morbidity rate was 33.3%, and there was no perioperative mortality. 46 cases were non-invasive IPMN, 32 cases were invasive IPMN including 14 cases with lymph node metastasis. The five-year survival rate for patients with non-invasive and invasive carcinomas was 96.2% and 35.2%, respectively. The prognosis of invasive cases with lymph node metastasis was significantly worse than those without lymph node metastasis. No progression was found during the follow-up in 18 asymptomatic small branch duct type IPMN patients.Conclusion : IPMN has a relative good prognosis. Main duct type and mixed type IPMN have a higher malignant potential, and should receive surgical treatment. Patients of branch duct type IPMN with lesion <3 cm in diameter and without clinical manifestations can be managed with close follow-up. Highlights: Evaluate our strategy of surgical treatments for different types of IPMN. IPMN has a relative good prognosis. Main duct type and mixed type IPMN should receive surgical treatment. Small branch duct type IPMN without clinical manifestations need no surgery.